Mulching and different levels of nitrogen and phosphorus improve yield and quality attributes of broccoli (Brassica oleracea var. italica) and physicochemical property of soil - Verma, Veerendra Kumar; Jha, Anjani Kumar; Verma, Bibhash Chandra; Chaudhuri, Priyajit; Nonglait, David (Vegetable Science, 2017)
A field experiment was conducted on broccoli (Brassica oleracea var. italic) hybrid Puspa during rabi season of 2013-14 to 2015-16 under the mid-hills of Meghalaya. The effect of mulching, different levels of nitrogen and phosphorous on the physicochemical properties of soil, yield and quality attributes of broccoli were studied. The treatments were consisting of nine nutrient combinationshaving three doses of N (Urea) and P2O5 (SSP) with and without mulching. The experiment was conducted in factorial randomized block design with three replications. The observations were recorded for growth, yield and quality attributes of plants and physicochemical properties of soil. All the growth, yield and quality attributes except vitamin-C and â-carotene increases with the increase in dosage of N and P fertilization under mulching condition. The results of mulching also have shown significant improvement in soil fertility parameters as well as yield and quality attributing traits. The treatment comprises of mulch (10 t/ha) + FYM (10 t/ha) + N120P80K60 gave higher gross plant weight (0.8 kg), marketable head weight (0.41 kg) and yield (16.6 t/ha) over the other treatments, could be recommended for the growers of the north eastern region for higher yield (18.4%) and profit.